THE EFFECT OF TRAINING AND COMPENSATION ON EMPLOYEE PERFORMANCE ON THE IMPLEMENTING DIRECTORS OF CONTROLLING THE DEVELOPMENT OF THE KEMAYORAN COMPLEX (DP3KK) - Florensia Herienda; Heny Ratnaningtyas; Reno Catelya Dira Oktavia (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
This study aims to determine the effect of training and compensation on employee performance. This type of research is descriptive research with a quantitative approach with multiple regression analysis methods, which is processed with the help of the SPSS program. The population and sample in this study were employees of the Executive Board of Directors of the Kemayoran Complex Development Control Company (DP3KK), who were the respondents. Data collection techniques by distributing questionnaires. The sampling technique used was the saturated sampling technique. The results of the study partially show that training and compensation have a significant effect on employee performance. This indicates that the training will help DP3KK employees improve their knowledge of skills and expertise in their fields, compensation by the expectations of DP3KK employees will be better, and performance results can be maximized. It is hoped that the leaders of the DP3KK companies formulate training explicitly and cover every aspect of the economy that can be quantified. It is hoped that the leaders of the DP3KK companies choose employees with an educational background suitable for their work; it is also recommended for employees to attend training/upgrades/workshops, and so on. other.Keywords: Training, Compensation, Employee Performance